The effect of oxygen concentration and temperature on nitrogenase activity in the heterocystous cyanobacterium Fischerella sp. - Lucas J. Stal (Nature Portfolio, 2017)
Abstract Heterocysts are differentiated cells formed by some filamentous, diazotrophic (dinitrogen-fixing) cyanobacteria. The heterocyst is the site of dinitrogen fixation providing the oxygen-sensitive nitrogenase with a low-oxygen environment. The diffusion of air into the heterocyst is a compromise between the maximum influx of dinitrogen gas while oxygen is kept sufficiently low to allow nitrogenase activity. This investigation tested the hypothesis that the heterocyst is capable of controlling the influx of air. Here, the thermophilic heterocystous cyanobacterium Fischerella sp. was analysed for the effects of oxygen concentration and temperature on nitrogenase activity. Dark nitrogenase activity is directly related to aerobic respiration and was therefore used as a measure of the influx of oxygen into the heterocyst. Above 30% O2, the influx of oxygen was proportional to its external concentration. Below this concentration, the influx of oxygen was higher than expected from the external concentration. A higher or lower temperature also triggered the heterocyst to increase or decrease, respectively, dark nitrogenase activity while the external concentration of oxygen was kept constant. A higher dark nitrogenase activity requires a higher rate of respiration and therefore a higher flux of oxygen. Hence, the heterocyst of Fischerella sp. is capable of controlling the influx of air.